Essays on human capital investments in Brazil - Lima, Lycia Silva e (2019)
Essay 1 - Public Childcare, Child Development and Labor Market Outcomes: Experimental Evidence from Rio de Janeiro, Brazil. This paper describes the short and medium term impacts of free public childcare provision in Rio de Janeiro using a lottery that allocated access to the program in 2008. Lottery winners had large gains in anthropometrics measures which persisted throughout time. They also had higher scores in cognitive function tests, which had faded out 7 years after the lottery took place. The program also had significant impacts on household income and employment outcomes of family members. Essay 2 - Are Public Schools Ready to Integrate Math Classes with Khan Academy? We study the impacts of the program Khan Academy in Schools using a randomized control trial in Brazilian primary public schools. Once a week, teachers would take their students to the school’s computer lab and teach using the Khan Academy platform, instead of their standard math classes. We find positive effects of the program on measures of attitudes towards math, which were not translated to a positive average treatment effect on students’ math proficiency. We also explore treatment heterogeneity by quality of implementation, suggesting that the program can have positive effects when there are no infrastructure problems and when the implementation modality is based on one computer per student. Essay 3 - Human Capital Investments Among Vulnerable Youth in Rio de Janeiro: Experimental Evidence from the Protejo Program. This paper presents experimental evidence to describe the impacts of the Project of Youth Protection in Vulnerable Territories (Protejo), implemented in Rio de Janeiro under the coordination of the Ministry of Justice with the purpose of fostering cognitive and noncognitive skills of youth participants to promote education and employment and, ultimately, reduce crime and victimization. Our results indicate that, although we find no average effects on education or noncognitive skills two years after the program, the intervention was successful in increasing beneficiaries’ probability of formal employment from 3 years after the end of the program onwards.